Fire service hydraulics - Casey, James F.; Shepperd, Fred. 1892- (R.H. Donnelley Corp., 1970)
"This time-honored classic has been used to help instruct personnel throughout the country in the science and art of fire service hydraulics. The fundamentals of hydraulics are unchanging. Topics discussed include water distribution systems, friction loss calculations, discharge and nozzle pressures, fire streams, standpipe systems, sprinkler systems, and foam systems."--publisher
Based on Fire service hydraulics, by Frederick Shepperd.
Keywords: Hydraulics.; Fire extinction.; elektronické knihy; electronic books